(untitled) (Global Journal of Science Frontier Research, 2019)
Allan Zade, the father of Z-Theory that was published in the form of a book in the US and UK in 2011, explains today an idea of a new device that was disclosed in the form of an international patent application as a Signal Medium Motion Measurement Apparatus (SMA).